Pengaruh Komunikasi, Reward, dan Lingkungan Kerja Terhadap Kinerja Karyawan Dengan Motivasi Kerja Sebagai Perantara - Rowiyani Rowiyani; Alfin Muslikhun; Mukhlidin Mukhlidin; Khoerul Soleh (Jurnal Publikasi Manajemen Informatika, 2024)
Employee performance is an important factor in achieving organizational goals, especially in a cooperative environment. This research aims to analyze the influence of communication, rewards and work environment on employee performance with work motivation as an intervening variable. The research approach used was explanatory research with a census method, involving 51 respondents who were employees of KSP Bhina ​​Raharja Papahan Karanganyar. Data analysis was carried out using path analysis to test direct and indirect relationships between variables. The research results show that rewards have the most dominant influence on employee performance, both directly and through work motivation. Meanwhile, communication has a negative influence on performance, and the work environment has a positive but not significant influence. Work motivation is proven to be an intervening variable that strengthens the relationship between rewards and employee performance. These findings have the implication that human resource management in cooperatives must place more emphasis on an effective reward system to increase employee motivation and performance.